2021
DOI: 10.1002/ardp.202100051
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and pharmacological characterization of some 2‐substituted‐3‐phenyl‐quinazolin‐4(3H)‐one derivatives as phosphodiesterase inhibitors

Abstract: Some 3‐phenyl‐quinazolin‐4(3H)‐one‐2‐thioethers (3a–e, 5a,b, 7a–e, 9a–d, 10a–d, and 12) along with 2‐aminoquinazoline derivatives 13a–c were prepared and screened for their in vitro phosphodiesterase (PDE) inhibitory activity. Some compounds such as 7d,e, 9a,b,d, 10a,d, and 13b exhibited promising activity as compared with the non‐selective PDE inhibitor IBMX. This inhibitory activity was validated by molecular docking in the active site of PDE7A and PDE4 to investigate their selectivity. Furthermore, the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Additionally, it has been observed that all these quinazoline derivatives possess significant anti-inflammatory activity ( Figure 1 ). It is worth knowing that PDE7 is a cAMP-specific phosphodiesterase enzyme ( Keravis and Lugnier, 2012 ; Amin, et al, 2021 ). PDE7 consists of two members, one of them is PDE7A, which is widely expressed in skeletal muscle and T-lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been observed that all these quinazoline derivatives possess significant anti-inflammatory activity ( Figure 1 ). It is worth knowing that PDE7 is a cAMP-specific phosphodiesterase enzyme ( Keravis and Lugnier, 2012 ; Amin, et al, 2021 ). PDE7 consists of two members, one of them is PDE7A, which is widely expressed in skeletal muscle and T-lymphocytes.…”
Section: Introductionmentioning
confidence: 99%